2013
DOI: 10.1007/978-3-642-39112-5_84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Meta-tutor for Constructing Models of Dynamic Systems

Abstract: While modeling dynamic systems in an efficient manner is an important skill to acquire for a scientist, it is a difficult skill to acquire. A simple step-based tutoring system, called AMT, was designed to help students learn how to construct models of dynamic systems using deep modeling practices. In order to increase the frequency of deep modeling and reduce the amount of guessing/gaming, a meta-tutor coaching students to follow a deep modeling strategy was added to the original modeling tool. This paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The research community has identified several types of strategies based on the tasks for which they are designed. For example, strategies may be (1) cognitive (e.g., a strategy for solving an addition problem); (2) metacognitive (e.g., a strategy for monitoring one's own cognitive operations when working on an equation-solving task), (3) focused on management (e.g., managing one's environment to promote focused attention); (4) directed toward learning (e.g., a strategy that facilitates learning of feedback processes); or (5) a combination of the four strategy types discussed above [29], [30]. For example, a metacognitive learning strategy may involve activating prior knowledge before learning about a topic by consciously bringing to mind information one already knows about the topic [31].…”
Section: Background: Metacognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research community has identified several types of strategies based on the tasks for which they are designed. For example, strategies may be (1) cognitive (e.g., a strategy for solving an addition problem); (2) metacognitive (e.g., a strategy for monitoring one's own cognitive operations when working on an equation-solving task), (3) focused on management (e.g., managing one's environment to promote focused attention); (4) directed toward learning (e.g., a strategy that facilitates learning of feedback processes); or (5) a combination of the four strategy types discussed above [29], [30]. For example, a metacognitive learning strategy may involve activating prior knowledge before learning about a topic by consciously bringing to mind information one already knows about the topic [31].…”
Section: Background: Metacognitionmentioning
confidence: 99%
“…For example, Zhang and colleagues [30] instructed students in the use of a target node strategy while constructing system dynamics models and then measured their use of that strategy. Results showed that in one experiment, 34% and 39% of students' steps (in two different groups) were consistent with the strategy.…”
Section: Background: Strategy Understandingmentioning
confidence: 99%
“…A first task model was created to represent learner's activity on software without the presence of the meta-tutor. This corresponds to the first version of software, which was evaluated against the interface including the meta-tutor in [18]. This second software interface includes a text-based agent that intervenes as the students engage in modeling to help them achieve deeper modeling behaviors, by applying constraints to the user's actions and giving meta-cognitive feedback.…”
Section: Conditions On Tasksmentioning
confidence: 99%
“…The meta-tutor requires students to follow a goal-reduction problem solving strategy, the Target Node Strategy [18]. The basic idea is to focus on one node at a time (the target node) and completely define it before working on any other node.…”
mentioning
confidence: 99%
“…This paper describes the design, development, implementation and evaluation of an intelligent online tutoring system (TS) (Chrysafiadi and Virvou ; Kularbphettong et al ; Zhang et al ) designed to teach or to remind math concepts essential for the integration of students of engineering, economics, management, among others, in mathematics higher education. The TS, which we developed in MITO platform, consists of small self‐paced modularized units of educational contents including tutorial videos, notes and formative e‐assessments with personalized feedback.…”
Section: Introductionmentioning
confidence: 99%